Monitoring / bioaccumulation of cadmium by fontinalis antipyretica (aquatic moss) - Martins, Ramiro (2011)
The purpose of this study is to understand quantitatively and qualitatively the accumulation and release of Cd (II) in aqueous solution by aquatic bryophytes - Fontinalis antipyretica - as in rivers biomonitoring as in the decontamination of industrial effluents . The cadmium accumulation and subsequent elimination by moss was studied in laboratory by exposing plants to different concentrations of metal in the range 0.5 - 2.5 mg l-1 for a contamination period of 144 h and then exposed to water free of metal during a decontamination of 192 h. A first order mass transfer kinetic model was fitted to experimental data.